Lavandula Angustifolia Mill. of Ukrainian origin: a comparative study of the chemical composition and antimicrobial potential of herb extracts - Bogatyrova, Olena; Hurina, Viktoriia; Naboka, Olga; Filimonova, Nataliia; Dzhoraieva, Svitlana; Mykhailenko, Olha; Georgiyants, Victoriya (ScienceRise: Pharmaceutical Science, 2024)
Provide updated data on the antimicrobial activity and chemical composition of original dry extracts from Lavandula angustifolia herb of Ukrainian origin. The aim – an experimental comparative study of the chemical profile and antimicrobial activity of the original dry extracts of Lavandula angustifolia herb and their effect on the ability to destroy biofilms of microbial cultures or prevent their formation in vitro. Materials and methods. The objects of the study are dry extracts obtained from the lavender herb with purified water and ethanol solutions (40 and 70 %). The main biologically active substances (BAS) of the extracts were determined by the Thin-layer chromatography and Absorption spectrophotometry methods. The microbiological properties of the test samples of the investigated plant extracts were studied in vitro by the two-fold serial dilutions method. The ability of microorganisms to form a biofilm was determined by the method of adhesion to polystyrene in flat-bottomed plastic plates. The optical density of the initial bacterial suspension was measured on the Densi-La-Meter device, and the density of inoculated bacterial cells on the Multiskan EX photometer at a wavelength of 540 nm. The study of the antimicrobial activity of water and ethanol extracts of lavender herb in a wide range of concentrations was carried out by the agar diffusion method in the "wells" modification, which is commonly used in microbiological practice. Results. Water and water-ethanol extracts of lavender of Ukrainian origin were obtained. Terpenoids (linalool, linylyl acetate and traces of 1,8-cineol), flavonoids (hyperoside, isoquercitrin), and hydroxycinnamic acids (rosmarinic, chlorogenic acids) were identified in the extracts. The total content of phenolic compounds is 2.02–2.60 mg/g, flavonoids – 1.46–3.17 mg/g. The largest amount of BAS was extracted with 70 % ethanol. According to the results of experimental studies, the extracts of the lavender herb, obtained by extraction with a water-ethanol solution (40 and 70 % ethanol) at a concentration of 1 mg/ml, have antimicrobial properties against a wide range of infectious agents (S. aureus, E. coli, K. pneumoniae, P. aeruginosa, C. albicans). Studies of the influence of test samples of lavender extracts at a concentration of 1 mg/ml on the ability of microorganisms (S. aureus, E. coli, K. pneumoniae, P. aeruginosa) to form biofilms demonstrated that the highest inhibitory activity against biofilm formation was found in the case of the action of test of a sample of phytoextract obtained by extraction with a water-ethanol solution (40 % ethanol), which accounted for S. aureus ‒ 57.8 %, P. aeruginosa – 66.7 %. A wide spectrum of antimicrobial action was established for the tested lavender phytoextracts under the conditions of application of the concentration range of 10-60 μg/ml. The best spectrum of antimicrobial action and the highest activity corresponds to the lavender extract, obtained by extraction with 70 % ethanol, with the effect depending on the concentration. Conclusion. The lavender herb of Ukrainian origin is a promising and affordable source of potential antimicrobial active pharmaceutical ingredients (API). Water-ethanol lavender extract (70 % ethanol), according to research results, has shown high antimicrobial and antifungal potential. According to preliminary data, antimicrobial activity correlates with the content of phenolic compounds. The obtained results may be useful for the search for original substances for the complex correction of symptoms of neurological deficits of infectious etiology